Influence of citrate on phase transformation and photoluminescence properties in LaPO4 and LaPO4:Eu. Issue 62 (19th October 2018) - Wu, An-Ping; Bai, He; Bao, Jin-Rong; Yang, Kui-Suo; Feng, Li-Na; Ma, Yang-Yang; Qiao, Yan; Li, Wen-Xian; Liu, Ying; Zhu, Xiao-Wei
Abstract : The hexagonal and monoclinic phase LaPO4 :Eu nanostructures have been controllably synthesized using a citrate-induced hydrothermal process at 100 °C. Abstract : The hexagonal and monoclinic phase LaPO4 and LaPO4 :Eu nanostructures have been controllably synthesized by a citrate-induced hydrothermal process at 100 °C. The crystal growth of LaPO4 nanostructures was investigated, and the phase transformation of nanostructured LaPO4 was systematically studied by varying the citrate concentration, pH value and reaction temperature. When 0.8 mmol of citrate was added into the reaction system, the hexagonal phase LaPO4 transformed into the monoclinic phase. High concentrations of citrate would lead to the formation of hexagonal phase LaPO4 . The photoluminescence properties of the monoclinic phase LaPO4 :Eu prepared using a citrate-induced process demonstrate that the electric dipole transition ( 5 D0 → 7 F2 ) is stronger than the magnetic dipole transition ( 5 D0 → 7 F1 ), which indicated that Eu 3+ is in a site with no inversion center. The strongest emission peak of hexagonal phase LaPO4 :Eu comes from 5 D0 → 7 F1 . Furthermore, the citrate-induced hexagonal phase LaPO4 :Eu has a stronger emission intensity than the hexagonal phase LaPO4 :Eu prepared not using a citrate-induced process.